Purification and characterization of xanthine oxidase from liver of the water buffalo Bubalus bubalis - Mahmoud A. Ibrahim, Hassan M.M. Masoud, Doaa A. Darwish, Sayed S. Esa, Samir A.M. Zaahkouk (Journal of Applied Pharmaceutical Science, 2015)
Xanthine oxidase (XO) is an important enzyme with broad medical applications as detecting reagent in many diagnostic kits. In this study, buffalo liver xanthine oxidase (BLXO) was purified to homogeneity by acetone precipitation and chromatography on DEAE-cellulose and Sephacryl S-300 columns with a specific activity of 7.2 units / mg protein which represent 31.3 folds. The native molecular weight of the purified enzyme is 200 kDa and its subunit molecular weight was determined by SDS-PAGE to be 67 kDa. The isoelectric point (pI) value of BLXO isoenzyme is at pH 6.0 – 6.2. It displayed its pH optima at 7.6 and the Km value is 1.1 mM xanthine. FeCl2 increased the activity of BLXO while CuCl2, MnCl2 and ZnCl2 were found to be inhibitors of the purified enzyme. Allopurinol inhibits BLXO competitively and has one binding site on it with Ki value of 0.025mM.
Keywords: Xanthine oxidase, Purification, Characterization, Buffalo liver, Medical applications.